Copigmentation of Black Rice Anthocyanin Extract and Steam Soybean Polyphenols: Phytochemical Analysis and Antioxidant Activity - Syafitri, Liza; Rais, Ichwan Ridwan; Salamah, Nina (Pharmaceutical Journal of Indonesia, 2026)
Introduction: Black rice (Oryza sativa L. indica) and soybean (Glycine max L. merr) have potential as sources of natural antioxidants due to their bioactive compounds. Objectives: This study aims to evaluate the antioxidant activity of black rice extract co-pigmented with steamed soybean extract and determine the effect of solvent variation on the antioxidant activity. Methods: The extraction process was carried out using several solvent variations, namely 70% ethanol, a combination of 70% ethanol with 3% citric acid solution, and a combination of 70% ethanol with 5% citric acid solution. Extract characterization includes yield, organoleptic properties, total polyphenols, total anthocyanins, and antioxidant activity for black rice extract. Antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Results: The results showed that black rice extract with a combination of 70% ethanol solvent and 5% citric acid had the highest antioxidant activity with an IC₅₀ value of 136.456±0.022 ppm (medium category), followed by extracts with a combination of 70% ethanol and 3% citric acid (IC₅₀ = 2414±0.003 ppm), black rice extract with 70% ethanol (IC₅₀ = 2621±0.006 ppm), and soybean extract with 70% ethanol (IC₅₀ = 3252±0.006 ppm). Copigmentation of anthocyanin and polyphenol extracts with a ratio of 80:20 (black rice: soybean) produced the strongest antioxidant activity (IC50= 107± 0.0398 ppm) and the highest total polyphenol content (112.87±0.175 GAE/g). Conclusions: This study shows that copigmentation effectively improves the stability and functional activity of the combination of black rice extract and steam soybean extract.